Plasma concentrations and placental immunostaining of interleukin-10 and tumor necrosis factor-alpha as predictors of alterations in the embryo-fetal organism and the placental development of diabetic rats - Sinzato, Y. K. [UNESP]; Damasceno, Débora Cristina [UNESP]; Laufer-Amorim, R. [UNESP]; Rodrigues, M. M. P. [UNESP]; Oshiiwa, M.; Taylor, K. N.; Rudge, Marilza Vieira Cunha [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2011)
Interleukin-10 (IL-10) appears to be the key cytokine for the maintenance of pregnancy and inhibits the secretion of inflammatory cytokines such as tumor necrosis factor-alpha (TNF-alpha). However, there are no studies evaluating the profile of these cytokines in diabetic rat models. Thus, our aim was to analyze IL-10 and TNF-alpha immunostaining in placental tissue and their respective concentrations in maternal plasma during pregnancy in diabetic rats in order to determine whether these cytokines can be used as predictors of alterations in the embryo-fetal organism and in placental development. These parameters were evaluated in non-diabetic (control; N = 15) and Wistar rats with streptozotocin (STZ)-induced diabetes (N = 15). At term, the dams (100 days of life) were killed under anesthesia and plasma and placental samples were collected for IL-10 and TNF-alpha determinations by ELISA and immunohistochemistry, respectively. The reproductive performance was analyzed. Plasma IL-10 concentrations were reduced in STZ rats compared to controls (7.6 +/- 4.5 vs 20.9 +/- 8.1 pg/mL). The placental scores of immunostaining intensity did not differ between groups (P > 0.05). Prevalence analysis showed that the IL-10 expression followed TNF-alpha expression, showing a balance between them. STZ rats also presented impaired reproductive performance and reduced plasma IL-10 levels related to damage during early embryonic development. However, the increased placental IL-10 as a compensatory mechanism for the deficit of maternal regulation permitted embryo development. Therefore, the data suggest that IL-10 can be used as a predictor of changes in the embryo-fetal organism and in placental development in pregnant diabetic rats.
Keywords: IL-10; Mild diabetes; Placenta; Pregnancy; Streptozotocin; TNF-alpha